Understanding QRIS Adoption in MSMEs Culinary Sector: Examining Technology Determinants and Behavioral Intention - Suryo Luqman Hakim; Totok Haryanto (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This research looks into the factors that QRIS adoption of Micro, Small, and Medium Enterprises (MSMEs) in Purwokerto by examining the influence of perceived usefulness, perceived trust, user interface, and perceived ease of use on behavioral intention and its implications for the decision to use. The study addresses inconsistencies in previous digital payment adoption research by integrating technology-related and behavioral factors into a comprehensive model focused specifically on MSMEs. In a quantitative study, purposeful sampling was employed. manner, involving 166 MSME respondents who had an interest in using QRIS. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceived ease of use is the only factor that significantly influences behavioral intention, while perceived usefulness, perceived trust, and user interface do not show significant effects. Furthermore, behavioral intention has a strong favorable impact on the decision to use QRIS. These findings suggest that MSME adoption of digital payment technology is more strongly driven by operational simplicity and ease of learning rather than perceived benefits, trust, or interface quality. The research advances technological advancement adoption literature by demonstrating that the traditional assumption of the Model of Technology Acceptance, which positions perceived usefulness as the dominant determinant, is not fully applicable in the MSME context. In practical terms, the results indicate that digital payment providers and policymakers ought to give priority to system simplicity, user-friendly features, and digital education to increase QRIS adoption among MSMEs.